Freeze-thaw stability of enzyme-treated espasol - Ibarreta, Fatima Jhoan Sayson
ABSTRACT The study aimed to evaluate the stability of enzyme-treated espasol subjected to 5 sequential cycles of freezing (-18ºC, 48 h) and thawing (12 ºC, 24 h). An acceptable base espasol formulation from Jaraza, Aquino, and Jaraza (1998) was developed based on existing published literatures using multi-level sensory evaluation (n=35) with the following characteristics after 3 levels of sensory evaluation: between light brown and brown in color; neither opaque nor translucent; neither strong nor weak espasol odor; slightly sweet and slightly strong espasol flavor; slightly soft, chewy, smooth, and sticky. Enzyme treatments of 0.005 and 0.012% maltogenic alpha-amylase; 0.003% and 0.012% pentosanase to the base espasol formulation resulted in a general increase in physico-chemical characteristics and in sensory acceptability. The 0.003% pentosanase-treated espasol was selected since it obtained the highest mean acceptability ratings at 5% level of significance in all the textural attributes evaluated (n=35) and was found to be more stable and more acceptable at the end of 5 freeze-thaw cycles based on the results of net syneresis, physico-chemical, microbiological, and sensory analyses. The sensory characteristics of the espasol at the end of 5 freeze-thaw cycles in color, odor, flavor, and texture remained near the acceptable range determined in the 1st phase. This could indicate that espasol can be subjected even up to 5 freeze-thaw cycles. Further studies on the stability of espasol in sequential freeze-thaw cycles were recommended to estimate the potential of the product as a frozen convenience food item that has an extended shelf-life and is more accessible to consumers.